A clinical case of successful treatment of the dry form of age-related macular degeneratio - Dziuba , Alina; Skrypnychenko , Inna (The Ukrainian Scientific Medical Youth Journal, 2024)
the clinical case is an example of the effectiveness of low-energy pulsed chromatic LED therapy of green (505 nm), red (625 nm) and infrared (940 nm) ranges in the treatment of dry age-related macular degeneration, which was performed with the Spektra Light device (Version MARK III, Vision AidInc., Canada). The patient was examined before treatment, 1 month, 3 months and 6 months after treatment: visual acuity was determined, optical coherence tomography of the macular zone was performed, and the optical density of the macular pigment of both eyes was determined by heterochromatic flicker photometry using a Maculux praxis densitometer (Germany, Ebiga VISION GmbH). In a patient with age-related macular degeneration, after two short-term courses (2 sessions per day with a 5-minute break for 5 days) of low-energy LED therapy, visual acuity increased, the optical density of the macular pigment increased, and positive dynamics was noted in the scans of optical coherence tomography of the macular zone of the retina.